2012
DOI: 10.4319/lo.2013.58.1.0144
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the phenolic profile in the diatom Phaeodactylum tricornutum growing under copper and iron stress

Abstract: Fourteen phenolic compounds were identified and quantified in extracts derived from in vitro culture of Phaeodactylum tricornutum diatom growing in natural seawater (control) and in natural seawater containing the following added copper (Cu) and iron (Fe) metals: Cu(II) (315 nmol L 21 and 790 nmol L 21 ) and Fe(III) (900 nmol L 21 ). The cell concentration was 471% for the last day of culture (expressed as a percentage of the control) for diatoms exposed to iron, while diatoms exposed to copper showed cell den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 42 publications
8
67
0
Order By: Relevance
“…The activity of the extracts is not only dependent on the concentration of the phenolic compounds but also on the structure and nature of the compounds [32]. Several reports have suggested that the biological activity of the extracts is also dependent on the interaction among the phenolic compounds [33,34]. Tafesh et al [35] reported that hydroxytyrosol at 400 µg·mL −1 caused growth inhibition of the four bacterial isolate gram-positive ( Streptococcus pyogenes and Staphylococcus aureus ) together with the gram-negative ( Escherichia coli and Klebsiella pneumoniae ), while gallic acid at 200 and 400 µg mL −1 inhibited the growth of the S. aureus and S. pyogenes strains, respectively (no growth inhibition was observed for the gram-negative bacteria).…”
Section: Resultsmentioning
confidence: 99%
“…The activity of the extracts is not only dependent on the concentration of the phenolic compounds but also on the structure and nature of the compounds [32]. Several reports have suggested that the biological activity of the extracts is also dependent on the interaction among the phenolic compounds [33,34]. Tafesh et al [35] reported that hydroxytyrosol at 400 µg·mL −1 caused growth inhibition of the four bacterial isolate gram-positive ( Streptococcus pyogenes and Staphylococcus aureus ) together with the gram-negative ( Escherichia coli and Klebsiella pneumoniae ), while gallic acid at 200 and 400 µg mL −1 inhibited the growth of the S. aureus and S. pyogenes strains, respectively (no growth inhibition was observed for the gram-negative bacteria).…”
Section: Resultsmentioning
confidence: 99%
“…The flow rate was 1.0 mL min −1 and the system operated at 27°C. The phenolic compounds gallic acid, protocatechuic acid, (+) catechin, vanillic acid, (−) epicatechin and syringic acid, chlorogenic acid, gentisic acid, caffeic acid, p-coumaric acid, ferulic acid, rutin, myricetin and quercetin were quantified in line with previously reported methods (Rico et al 2013). In brief, a gradient system with two mobile phases was used as follows: eluent A was Milli-Q water with 0.1 % formic acid and eluent B was methanol.…”
Section: Solid-phase Extractionmentioning
confidence: 99%
“…Identification and quantification of natural polyphenols excreted by microorganisms are necessary to improve our knowledge about the biogeochemistry of metals in natural waters and the role of these ligands in the chemistry under metallic stress conditions. Rico et al (2013) reported differences in the phenolic profile of the diatom Phaeodactylum tricornutum harvested in natural seawater (control) and in natural seawater enriched with heavy metals (copper and iron). The profile was dependent upon the metal added to the culture media.…”
Section: Introductionmentioning
confidence: 98%
“…Exogenous organic substrate and heavy metal ion concentration are crucial factors influencing microbial EPS production and biofilm formation in these systems. For instance, silver ions and nanoparticles affect the composition of phototrophic biofilm in operated bioreactors (González et al., 2015), and copper and iron concentrations affect the profile of phenolic compounds exuded by marine microalgae (Rico et al., 2013, Lopez et al., 2015). …”
Section: Introductionmentioning
confidence: 99%